Genome-Wide Identification, Structural, and Gene Expression Analysis of BRI1-EMS-Suppressor 1 Transcription Factor Family in Cucumis sativus - Si Ma; Tingting Ji; Meiting Liang; Shihui Li; Yongqiang Tian; Lihong Gao (Frontiers in Genetics, 2020)
BRASSINOSTEROID INSENSITIVE1-EMS-suppressor 1 (BES1) is an essential regulator downstream of brassinosteroid signaling and plays important roles in plant stress response, growth, and development. To date, the regulation mechanisms of BES1 transcription factors have been identified and elucidated in model plants Arabidopsis and rice. However, little information is available regarding the BES1 family in Cucumis sativus. Therefore, this study conducted a genome-wide analysis of BES1 genes in cucumber. In cucumber, a total of six CsBES1 genes were identified, and their phylogenetic relationships, gene structures, and cis-elements in promoters were studied. CsBES1 genes were distributed on four of seven chromosomes. Gene structure analysis showed that the intron–exon model of CsBES1 genes was conserved and the CsBES1 protein contained a DUF822-conserved motif. Promoter cis-element prediction showed that plenty of developmental and stress- and hormone-related elements have been found in promoter regions of CsBES1 genes. Meanwhile, BES1 was divided into three groups (I, II, and III) on the basis of phylogenetic relationship analysis in six plant species. In addition, CsBES1 gene expression patterns were confirmed by transcription database and qRT-PCR analysis; the results showed that the expression of CsBES1 genes had not only tissue-specific expression but also different types of CsBES1 isoform which might respond to specific plant stresses. In summary, genome-wide identification, phylogeny, gene structure, and expression profile analysis of CsBES1 genes in cucumber provided a referable theoretical information for further functional study of CsBES1 genes and further facilitated the molecular breeding of cucumber.